Preliminary evidence that hippocampal volumes in monkeys predict stress levels of adrenocorticotropic hormone - Lyons, David M. (2007)
BACKGROUND: Hippocampal volumes previously determined in monkeys by magnetic resonance imaging are used to test the hypothesis that small hippocampi predict increased stress levels of adrenocorticotropic hormone (ACTH). METHODS: Plasma ACTH levels were measured after restraint stress in 19 male monkeys pretreated with saline or hydrocortisone. Monkeys were then randomized to an undisturbed control condition or intermittent social separations followed by new pair formations. After 17-months of exposure to the intermittent social manipulations, restraint stress tests were repeated to determine test/retest correlations. RESULTS: Individual differences in post-restraint stress ACTH levels over the 17-month test/retest interval were remarkably consistent for the saline (r(s)=0.82, P=0.0004) and hydrocortisone (r(s)=0.78, P=0.001) pretreatments. Social manipulations did not affect post-restraint stress ACTH levels, but monkeys with smaller hippocampal volumes responded to restraint after saline pretreatment with greater increases in ACTH levels with total brain volume variation controlled as a statistical covariate (β= −0.58, P=0.031). Monkeys with smaller hippocampal volumes also responded with diminished sensitivity to glucocorticoid feedback determined by greater post-restraint ACTH levels after pretreatment with hydrocortisone (β= −0.68, P=0.010). CONCLUSIONS: These findings support clinical reports that small hippocampi may be a risk for impaired regulation of the hypothalamic-pituitary-adrenal axis in humans with stress-related psychiatric disorders.